Educational topics for school from the perspective of professionals in the Mobile Emergency Service - Larissa Larie Mota; Selma Regina de Andrade (SciELO, 2016)
Objective To systematize, with professionals from the Mobile Emergency Care Service of Santa Catarina municipality, the main issues for the development of an educational tool of attention to the emergency room, dedicated to the school-age population. Method Qualitative study, conducted through meetings in the focus group format, with 19 professionals who develop their activities in the city Emergency Mobile Emergency Service. Data were categorized and analyzed using thematic analysis technique. Results The contents discussed at the meetings were grouped into four thematic categories: The Mobile Emergency Service and the school: education and health promotion for children; As the Mobile Emergency Care Service works: What is important to know ?; Something's wrong, what now? and; We are nearly finished, give your opinion. Conclusions The specific issues arising from the meetings contributed to the production of an educational tool on the activities of the Mobile Emergency Service, which may be used by the School Health Program to promote health education in the care area to the emergency room with the population schoolchildren.